Rancang Bangun Sistem Informasi Manajemen Kepegawaian Berbasis Web di CV. Awan Media Indonesia - Akbar, Ray Fatra Filahi; Nasruloh, Sofhian Fazrin (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to produce a web-based personnel management information system at CV. Awan Media Indonesia, as well as knowing the feasibility test for using the system. 1. How to create a Website-Based Personnel Management Information System at CV. Indonesian Media Cloud. 2. What is the Feasibility of Using a Website-Based Personnel Management Information System at CV. Indonesian Media Cloud. Research Design The research method used in this research refers to the R&D Model with the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. Because the research model and This development is more rational and complete compared to other models according to the product development steps. According to the survey questionnaire data that I collected, based on the results of the usability testing percentage with a score of 94.7%, it is in the "Strongly Agree" category and fulfills the usability aspect